First Bocchus Ashmead (Hymenoptera: Dryinidae) from Upper Eocene Rovno amber: B. schmalhauseni sp. nov. - Perkovsky, Evgeny E.; Olmi, Massimo; Vasilenko, Dmitry V.; Capradossi, Leonardo; Guglielmino, Adalgisa (Zootaxa, 2020)
A new species of pincer wasps, Bocchus schmalhauseni sp. nov. (Dryinidae) is described from Rovno amber (Ukraine). The amber piece was collected in the Vladimirets District in the north-west of the Rovno region. Taking into account this new record, a total of five species of Dryinidae are registered from Rovno amber. A key to the fossil species of Bocchus Ashmead is presented. The possible reasons for the different distribution of Dryinus species on both coasts of Subparathetys are discussed.